W.J.S. Pullen (1818 [sic]-1887) - Pullen, H.F. (ARCTIC, 1982)
Pullen had a long career as a naval officer and surveyor. He was persuaded to leave the Navy for a time, in which he was employed by the Surveyor General of South Australia. He later rejoined the Royal Navy and surveyed the Saint John River and Bay of Fundy. He was then appointed as first lieutenant of H.M.S. Plover, which was a depot ship for the first of three searches for Franklin. He birthed the Plover and two other ships at Wainwright Inlet and set out from there in boats, travelling east to the Mackenzie River. His men overwintered at Fort McPherson and Great Slave Lake. While on his way to York Factory in the spring, Pullen was met by two Indians with a commission from England requesting that he continue the search for Franklin east of the Mackenzie River. A second winter was spent up the Mackenzie River. His second arctic journey was made less than two years later, during which he commanded the H.M.S. North Star, as part of Sir Edward Belcher's 1852-54 expedition. During this expedition Pullen stayed two winters in Erebus and Terror Bay, Beechey Island, and travelled across Lancaster Sound and up Wellington Channel.